2016
DOI: 10.1002/cncr.30468
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of influenza vaccination during 3‐week cytotoxic chemotherapy cycles

Abstract: The antibody responses to influenza vaccination on days 1 and 11 during a 3-week cytotoxic chemotherapy cycle were comparable. Influenza vaccination can be performed concurrently with cytotoxic chemotherapy or during the cytopenic period. Cancer 2017;123:841-48. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 14 publications
1
28
1
1
Order By: Relevance
“…While some studies report a response rate similar to healthy subjects [ 43 , 54–56 ], the authors of the VACANCE trial suggest a second administration of influenza vaccine in cancer patients as this increased seroconversion from 44% to 73% [ 57 ], but further investigations are needed. It was recently shown that cancer patients can be vaccinated independent of chemotherapy and simultaneous administration vaccination and chemotherapy is possible [ 58 ].…”
Section: Disease Entity-specific Vaccination Strategiesmentioning
confidence: 99%
“…While some studies report a response rate similar to healthy subjects [ 43 , 54–56 ], the authors of the VACANCE trial suggest a second administration of influenza vaccine in cancer patients as this increased seroconversion from 44% to 73% [ 57 ], but further investigations are needed. It was recently shown that cancer patients can be vaccinated independent of chemotherapy and simultaneous administration vaccination and chemotherapy is possible [ 58 ].…”
Section: Disease Entity-specific Vaccination Strategiesmentioning
confidence: 99%
“…A study by Keam et al demonstrated that influenza vaccination, regardless of timing during 3‐week cytotoxic chemotherapy cycles, may provide seroprotection . The majority of patients in this study were women with either breast or lung cancer.…”
mentioning
confidence: 70%
“…A significantly higher response was observed in the breast cancer patients who were vaccinated on day 5 compared with those who were vaccinated on day 16, whereas no significant difference was found between the corresponding 2 groups of colon cancer patients 22 . Keam et al compared influenza vaccinations on day 1 and day 11 in lung or breast cancer patients on a 3‐wk cycle of chemotherapy, and they reported that the timing of vaccination made no significant difference for antibody production 23 . There have been various published recommendations on the timing of influenza vaccination, such as 2 wk before the start of chemotherapy, 17,24‐26 1 mo after chemotherapy, and when the amount of white blood cells has recovered to more than 1000 cells/mm 27 .…”
Section: Discussionmentioning
confidence: 99%